Some Technological and Functional Properties of Lactic Acid Bacteria Isolated from Hardaliye - Arici, Muhammet; Coskun, Fatma; Celikyurt, Gulnaz; Mirik, Mustafa; Gulcu, Mehmet; Tokatli, Nazan (ANKARA UNIV, FAC AGR, 2017)
Hardaliye is a lactic acid fermented beverage produced from red grape or grape juice with addition of crushed mustard seeds and benzoic acid and it is widely produced and consumed in the Thrace region of Turkey. The aim of this study was to determine the dominant lactic acid bacteria (LAB) species found in hardaliye and to investigate their technological properties related to probiotic action and potential use as a starter culture for production of hardaliye. For this aim; LAB were isolated from 28 hardaliye samples (23 hardaliye samples that were obtained from different regions of Kirklareli, Turkey and 5 hardaliye samples were produced by using traditional methods in laboratory conditions). After carrying out conventional and molecular biological methods, it was found that all LAB species isolated belonged to genus Lactobacillus. The dominant species in the microbiota was found to be Lactobacillus plantarum while around 98% of the isolates were similar to each other. Therefore, it was well understood that a small diversity of LAB strains played role during the fermentation process. The results of this study revealed that the isolates had the potential to be used as starter cultures in hardaliye production due to their antimicrobial effects and acid production capabilities.
Keywords: Hardaliye; Lactobacillus; Probiotic properties; Technological properties; ANTIBIOTIC SUSCEPTIBILITY; PROBIOTIC BACTERIA; HYDROGEN-PEROXIDE; BILE TOLERANCE; IN-VITRO; STRAINS; IDENTIFICATION; LACTOBACILLI; SELECTION; STARTER; Agriculture